2019
DOI: 10.1021/acssuschemeng.9b00652
|View full text |Cite
|
Sign up to set email alerts
|

Co-, Fe-, and N-Modified Carbon Composites for Excellent Catalytic Performances toward Electrochemical Reduction Reaction

Abstract: The development of highly active noble-metal-free nitrogen-doped carbon materials is of great significance to the industrial applications of renewable and sustainable energy. In this paper, core-shell structural carbon materials composed of nitrogen-doped carbon-shell-encapsulated iron–cobalt mixed metal carbides were obtained through pyrolysis of metal organic framework precursors. Metallic (Co, Fe) carbide nanoclusters embedded in nitrogen-doped hollow carbon spheres were obtained after most of the mixed met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…This difference may be responsible for the different activities of the Co–N/CNT/C catalysts. High-resolution XPS spectrum of C 1s reveals four peaks, including CC (284.8 eV), CN (285.0 eV), CO (286.0 eV), and CO (289.4 eV) . The presence of a CN bond further indicates the successful doping of nitrogen into carbon.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may be responsible for the different activities of the Co–N/CNT/C catalysts. High-resolution XPS spectrum of C 1s reveals four peaks, including CC (284.8 eV), CN (285.0 eV), CO (286.0 eV), and CO (289.4 eV) . The presence of a CN bond further indicates the successful doping of nitrogen into carbon.…”
Section: Resultsmentioning
confidence: 99%
“…34 The N 1s XPS spectrum of Ndoped carbon (NC) shows three peaks, which are assigned to pyridinic N (398.3 eV), pyrrolic-N (N2, 399.5 eV), and graphitic-N (N1, 400.9 eV) (Figure S10). 35 The presence of a CN bond further indicates the successful doping of nitrogen into carbon. Accordingly, the occurrence of the O 1s peak was attributed to CO (531.1 eV) and CO (533.3 eV) of the edge oxygen of the carbon matrix, 36 as well as SO (532.4 eV) of SO 4 2− anions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…21 Therefore, it is necessary to investigate the catalytic behaviors of different composites of iron oxide-graphene oxide-based materials to benchmark their catalytic activities, deepening the understanding of fundamental questions. 23 Ultrafine Fe 3 O 4 nanoparticles were grown through in situ deposition which can occupy a greater surface area, and smaller nanoparticles of the same total mass are necessary to increase the physicochemical properties. Parvez et al synthesized nitrogen-doped graphene decorated with Fe that showed an enhanced ORR catalytic activity better than metal-free nitrogen-doped graphene.…”
Section: Introductionmentioning
confidence: 99%
“…33,34 The basic approach of this novel method is to quench the oxidized nature and encounter in developing defect-free Fe− C and Fe−C−O sites which enable higher conduction and efficiency. 23,35 It also helps in curtailing the particle size and reduction of oxygen sites from the GO functional group which facilities the formation of a higher amount of Fe−C sites. 36 Also, Fe−C−O sites interfacing the secondary phase and increasing the active oxygen species sites on the surface to anchor with Fe− O are well facilitated for higher promotion of current and performance.…”
Section: Introductionmentioning
confidence: 99%
“…As alternative clean energy technologies, fuel cells and metal–air batteries have attracted significant attention. , The oxygen reduction reaction (ORR) in the cathode undergoes a sluggish process which determines the property of fuel cells. The platinum (Pt) catalysts are usually used as cathode materials for ORR, but its high cost, poor methanol tolerance, and durability restrict the development and wide use of the fuel cell technology. Therefore, the exploration of nonplatinum catalysts with both superb activity and satisfying stability has become the most important research topic. …”
Section: Introductionmentioning
confidence: 99%